An efficient approach to detect melanoma skin cancer using a custom CNN model - Rahman, K.M Saidur; Amin, Tanjim Bin; Rahman, Mahdi Sakib; Sakib, G M Shadman Hossain (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.